Produksi dan Kestabilan Pigmen Merah Kapang Monascus sp. Menggunakan Media Tepung Kulit Singkong dengan Penambahan Bekatul pada Konsentrasi yang Berbeda - Sona Fatimah; Agung Suprihadi; Endang Kusdiyantini (Jurnal Akademika Biologi, 2014)
The used of synthetic dyes have a various of negative effects on human health. Pigment produced by Monascus sp. can be used as an alternative natural coloring food. The purpose of this research is to produce pigment Monascus sp. using the substrate cassava peels flour with the addition of rice bran at various concentrations. The study was conducted by growing Monascus sp. on medium cassava peels flour with the addition of rice  bran in various concentrations (0%, 2.5%, 5% and 10%). Measured parameter is the production of red pigment and pigment stability against temperature, water content, solubility and pH. Red pigment production was measured using a spectrophotometer with a wavelength of 500 nm. Analysis of the data using One Way ANOVA and Duncan test. The results showed that the highest production of red pigment (5.6 CVU / gds) and water content of 47% was obtained on medium cassava peels flour with rice bran addition of 10%. Pigment stability towards heat are 0,39 at 300C, 0,35 at 600C, 0,27 at 1210C, and 0,22 at 1500C , stability pH 3 are 0,37 (0 hours incubation) dan 0,26 (12 hours incubation) whereas pH 7 are 0,38 (0 hours incubation) dan 0,36 (12 hours incubation).Keywords: Fermentation,Cassava peels flour, Rice bran, Monascus, Pigment intensity, stability